How painful is a recession? An assessment of two future-oriented buffering mechanisms. (June 2020) - Wilkinson, Lindsay R.; Schafer, Markus H.; Wilkinson, Renae
Abstract: Rationale and objective: Guided by stress process theory, this study investigates the association between the economic downturn and chronic pain interference, as well as the role of two future-oriented buffering mechanisms (anticipated stressor duration and pre-recession financial optimism) in this relationship. This research integrates both an objective measure of the recession based on negative personal experiences, as well as subjective event-based appraisals of how the recession impacted people's lives. Method: Drawing on longitudinal data from the National Survey of Midlife Development in the United States, linear lagged dependent variable models are used to estimate associations between recession-era stressors and chronic pain interference among 1113 adults. The analysis further examines the moderating influences of anticipated stressor duration and pre-recession financial optimism. Results: Findings reveal that both an accumulation of adverse experiences and global appraisals of the economic recession have harmful associations with chronic pain interference; however, their magnitude varied according to future-oriented moderating factors. Specifically, people with high pre-recession financial optimism fared better when confronted with recession-related stressors than did those with low levels of financial optimism. Moreover, pain interference was greater among individuals who appraised the recession as having a negative impact on their lives, but only if they perceived the recession would extend into the future. Conclusions: This study demonstrates distinctive links between two recession-related measures and pain interference. Findings suggest that positive future orientations can be protective during an economic crisis, whereas negative orientations heighten the pain. Highlights: Perceiving the 2008 recession as a severe hardship was linked to heightened pain. Painfulness of the recession was magnified when people believed it would linger. Financial optimism lessened the painfulness of stressors during the recession. Positive future orientations may be protective during economic crises.